2021
DOI: 10.1126/sciadv.abf4100
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signaling in AgRP neurons regulates meal size to limit glucose excursions and insulin resistance

Abstract: The importance of hypothalamic insulin signaling on feeding and glucose metabolism remains unclear. We report that insulin acts on AgRP neurons to acutely decrease meal size and thereby limit postprandial glucose and insulin excursions. The promotion of insulin signaling in AgRP neurons decreased meal size without altering total caloric intake, whereas the genetic ablation of the insulin receptor had the opposite effect. The promotion of insulin signaling also decreased the intake of sucrose-sweetened water or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…[78][79][80] Instead, the gradual suppression of feeding observed during ARC AGRP neuronal inhibition in the food intake experiment functionally validates the strategy indicating that there was sufficient chemogenetic inhibition of these neurons and accords with previous reports that the suppression of feeding by ARC AGRP neuronal inhibition is related to premature cessation of feeding rather than a generalized decrease in feeding. 9,25,[81][82][83] Of note, our chemogenetic inhibition of ARC AGRP neurons in this study caused the exact same pattern of suppressed feeding as previously observed. 25 As such, current evidence suggests that the more subtle behavioral effects of ARC AGRP inhibition are not related to technical issues but are simply a byproduct of the primarily unidirectional appetitive effects of ARC AGRP circuitry on food intake.…”
Section: Articlesupporting
confidence: 66%
“…[78][79][80] Instead, the gradual suppression of feeding observed during ARC AGRP neuronal inhibition in the food intake experiment functionally validates the strategy indicating that there was sufficient chemogenetic inhibition of these neurons and accords with previous reports that the suppression of feeding by ARC AGRP neuronal inhibition is related to premature cessation of feeding rather than a generalized decrease in feeding. 9,25,[81][82][83] Of note, our chemogenetic inhibition of ARC AGRP neurons in this study caused the exact same pattern of suppressed feeding as previously observed. 25 As such, current evidence suggests that the more subtle behavioral effects of ARC AGRP inhibition are not related to technical issues but are simply a byproduct of the primarily unidirectional appetitive effects of ARC AGRP circuitry on food intake.…”
Section: Articlesupporting
confidence: 66%
“…Where indicated, mice were administered vehicle or SS31 (Selleckchem, Houston, TX) at 2 mg/kg per day (intraperitoneally) for five consecutive days before ITTs. Blood was collected from conscious fed [satiated, 11:00 p.m. ( 57 , 58 )] and 6-hour fasted mice by submandibular bleeding; plasma insulin levels were determined using the mouse insulin enzyme-linked immunosorbent assay (ELISA; ALPCO, Salem, NH) or an in-house ELISA (Monash Antibody Technologies Facility), and the corresponding blood glucose levels were determined with an Accu-Check glucometer. Food intake, wheel running, and energy expenditure were assessed over 72 hours after 24-hour acclimation using the Promethion Metabolic Screening System (Sable Systems International, North Las Vegas, NV) fitted with indirect open circuit calorimetry, running wheels, and food consumption and activity monitors.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, studies have shown rapid activation of IRS-1/PI3K/Akt signaling in AgRP/POMC neurons after peripheral insulin injection [75]. Although the exact neuronal circuitry and glial cell contributions remain to be determined, recent advances in the field highlight the complex interplay between insulin and leptin (adipose tissue-derived hormone) in the regulation of feeding behavior and metabolic homeostasis in otherwise healthy or obese male mice [76, 77]. Furthermore, the activation of NMDA receptors on NTS neurons by insulin has been demonstrated to feed input into the hypothalamus which is required to lower glucose production by the liver as well as reduce feeding behavior [78, 79].…”
Section: Insulin and Insulin Resistance In The Cnsmentioning
confidence: 99%